2018
DOI: 10.1002/cam4.1500
|View full text |Cite
|
Sign up to set email alerts
|

Genomic characterization of individuals presenting extreme phenotypes of high and low risk to develop tobacco‐induced lung cancer

Abstract: Single nucleotide polymorphisms (SNPs) may modulate individual susceptibility to carcinogens. We designed a genome‐wide association study to characterize individuals presenting extreme phenotypes of high and low risk to develop tobacco‐induced non‐small cell lung cancer (NSCLC), and we validated our results. We hypothesized that this strategy would enrich the frequencies of the alleles that contribute to the observed traits. We genotyped 2.37 million SNPs in 95 extreme phenotype individuals, that is: heavy smo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Increased neutrophil numbers, as well as high MPO and cytokine levels in BAL fluid, are hallmarks of the inflammatory response in ALI. Interestingly, recent genome-wide association studies indicated that PDE10A is a candidate gene for asthma in mice and human (49,50) as well as smoking-induced lung cancer (51). Thus, our current findings together with previous reports suggest a critical role of PDE10A induction in pulmonary pathology.…”
Section: Discussionsupporting
confidence: 84%
“…Increased neutrophil numbers, as well as high MPO and cytokine levels in BAL fluid, are hallmarks of the inflammatory response in ALI. Interestingly, recent genome-wide association studies indicated that PDE10A is a candidate gene for asthma in mice and human (49,50) as well as smoking-induced lung cancer (51). Thus, our current findings together with previous reports suggest a critical role of PDE10A induction in pulmonary pathology.…”
Section: Discussionsupporting
confidence: 84%
“…In a previous study we applied the same methodology, studying as extreme cases individuals with non-small lung cancer, rather than exclusively adenocarcinoma; and assessing the germline DNA through Genome Wide Association Study (GWAS) (39). We identified and validated two new genetic variants in ATP10D and PDE10A which were differentially expressed in individuals presenting the extreme phenotypes assessed, and we confirmed the prognostic relevance of the associated proteins in early stage non-small cell lung cancer.…”
Section: Discussionmentioning
confidence: 65%
“…95 Clinical applications aside, these susceptibility genes do provide an insight into the biological process and association with specific diseases, which are relevant to lung cancer etiology. 96,97 Clearly, there is a wealth of information captured within the current genome-wide association studies' data sets. Taking advantage of it will depend on state-of-the-art mathematical and statistical approaches capable of incorporating large numbers of single-nucleotide polymorphisms into risk models, artificial intelligence, and supervised machine learning approaches.…”
Section: Genetic Predisposition To Lung Cancermentioning
confidence: 99%